Dampak Penambangan Pasir Terhadap Kerusakan Lingkungan - Muhammad Al Mi’raj Rawa; La Harudu; La Ode Nursalam; Andrias Andrias (Jurnal Penelitian Pendidikan Geografi, 2025)
Puusangi Village is an area with sand mining activities using suction machines, which have generated significant environmental impacts. This study aims to examine the effects of sand mining in the Konaweha River on environmental degradation in Puusangi Village, Anggalomoare District, Konawe Regency, employing a descriptive quantitative approach combined with Maxar satellite imagery analysis. The findings reveal road damage, a decline in fish populations, morphological changes in the river such as widening and channel shifts, and increased risks to infrastructure due to riverbank erosion. Analysis of Maxar imagery from 2014, 2019, and 2024 shows significant changes, including accretion, channel shifts, and narrowing distance between the riverbank and the road, indicating high-intensity sand mining activities. These results imply the urgent need for sustainable mining management and environmental mitigation policies to prevent further degradation. In conclusion, this study highlights that sand mining in Puusangi Village not only causes physical damage to the river but also poses serious socio-economic threats that require immediate attention.